Social pleasures of music - Nummenmaa Lauri; Putkinen Vesa; Sams Mikko (Elsevier Ltd, 2022)
Humans across all societies engage in music-listening and making, which they find pleasurable, despite music does not appear to have any obvious survival value. Here we review the recent studies on the social dimensions of music that contribute to music-induced hedonia. Meta-analysis of neuroimaging studies shows that listening to both positively and negatively valenced music elicit largely similar activation patterns. Activation patterns found during processing of social signals and music are also remarkably similar. These similarities may reflect the inherent sociability of music, and the fact that musical pleasures are consistently associated with autobiographical events linked with musical pieces. Brain’s mu-opioid receptor (OR) system governing social bonding also modulates musical pleasures, and listening to and making of music increase prosociality and OR activity. Finally, real or simulated interpersonal synchrony signals affiliation, and accordingly music-induced movements increase social closeness and pleasant feelings. We conclude that these links between music and interpersonal affiliation are an important mechanism that makes music so rewarding.